Historical and Pedagogical Research of Primary Education Development in Transcarpathia Region in the Second Half of the XIX Century – the First Half of the XXІ Century: Basic Approaches - Fizeshi, Oktaviya (Pedagogical Discourse, 2013)
The article considers some peculiarities of use of main approaches (systematic, chronological, formatioal, сivilizational, synergistic) to research primary education development in Transcarpathia region in the second half of the XIX century – the first half of the XXІ century.